Proof-of-Concept Study for Reflectance Pulse Oximetry Using Optical-Fibre-Based Sensors - Annaheim Simon; Braun Fabian; Bernhard Leah; Pfammatter Amarin; Proença Martin; Bonnier Guillaume; Ferrario Damien; Lemay Mathieu; Rossi René M. (Current Directions in Biomedical Engineering, 2022)
Optical fibres enable to design of new textile-based sensors for an unobtrusive, continuous, and long-term acquisition of photoplethysmography (PPG) signals. However, no research has been done about the accuracy of measuring blood oxygen saturation (SpO2) and the feasibility of PPG-based blood pressure measurement. This proof-ofconcept study examined these aspects for a woven sensing patch applied on the forehead in five healthy participants. During a controlled desaturation study, SpO2 estimation revealed an amplitude of the root-mean-squared error (ARMS) of 3.6%, and acceptable signal quality for blood pressure estimation was achieved for 40% of all data. These results indicate that textile-based sensors can reach the required PPG signal quality to simultaneously estimate multiple vital signs, including blood pressure.